Passive Direct Methanol Fuel Cell Stack: Design and Performance Characteristics - Zainoodin, A.M.; Kamarudin, S.K.; Masdar, M.S. (Advanced and Sustainable Technologies (ASET), 2026)
In this study, passive direct methanol fuel cell (DMFC) stacks consisting of six cells with a porous carbon nanofiber (CNF) anode diffusion layer have been successfully designed, fabricated, and tested. The performance of the passive DMFC stacks connected in series was tested and compared for mono-polar and bi-cell designs. Each stack consisted of six MEAs with an active area of 4 cm2 each and was tested at ambient temperature using 3 M diluted methanol. The experimental results indicate that the mono-polar stack exhibited higher performance, with a maximum power of 550 mW, which was 23.8% higher than that of the bi-cell stack. The output voltage can be maintained at approximately 2 V for 7 h with 21 ml of 3 M diluted methanol at a constant current discharge of 60 mA. Furthermore, it can be observed that both stacks display a stable and reproducible performance, which can be restored once the fresh methanol is refilled. Additionally, it can be observed that the difference in cell efficiency between the two stacks is less substantial. Overall, only approximately 35% of the methanol was utilized in each stack.